A Spongy Appetite: A Case of Pica - Miranda Paulo, Inês; Marques, Carla; Serra, Mariana; Âmbar Botelho, Carlota; Alcoforado, Ana; Pires, Catarina M (Curēus (Palo Alto, CA), 2024)
Pica is an eating disorder defined as the compulsive and repeated ingestion of substances that have no nutritional value for at least one month. This condition may be hard to diagnose without complications, as a high degree of suspicion is needed. The subject in this case was a teenager who presented with asthenia and unspecific abdominal pain. The etiological workup showed no abnormalities other than mild anemia and iron and folate deficiencies. After a thorough anamnesis, the patient's mother mentioned sporadic ingestion of synthetic mattress foam since childhood, which had become more frequent in the previous year. With this key information, it was possible to establish a diagnosis before serious complications occurred and thus help the patient get the necessary assistance by referring them to pediatrics, nutrition, and child and adolescent psychiatry consultations. This case report highlights the importance of a detailed anamnesis, particularly when dealing with unspecific symptoms, exploring the possibility of disorders that are rarely thought of, such as pica. It also recaps how important it is to address sensitive topics like eating disorders and create an open environment with no judgment, as these attitudes are crucial to ensuring the correct diagnosis and providing the best care for patients.